2017
DOI: 10.4314/jasem.v21i5.14
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characteristics and heavy metal levels in soil samples obtained from selected anthropogenic sites in Abeokuta, Nigeria

Abstract: This study assessed the effect of heavy metals introduced into the soils through human activities which can bio-accumulate in plants and passed to man via the food chain that can pose health risk. Topsoil samples were collected from selected anthropogenic and control sites (dumpsites, mechanical workshops, abattoirs, fuel filling stations and hospital incinerators) in Abeokuta, Nigeria at the depths 0-5cm, 5-10cm and 10-15cm. Physicochemical parameters such as pH, moisture content, bulk density, organic matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 14 publications
3
21
2
Order By: Relevance
“…Peasant community "Purísima Concepción de Paccha" (CCP-LO), of Yauli province, Junín-Peru, is situated between South Latitude 11 ° 31´03" and West Longitude 75 ° 53´58" (altitude 3,700) and located 10.2 km from metallurgical complex La Oroya (Figure 2), industry dedicated to poly-metallic transformation (copper, zinc, silver, lead, indium, bismuth, gold, selenium, tellurium and antimony), that emits fine particulate material (PM), loaded with heavy metals that pollute the ecosystem for more than nine decades [23,24]. PM rich in Pb and other heavy metals is deposited in the soil and water resources, and being easy transferred to the plants [25,26,17]. Figure 2 shown the geographical location o the CCP-LO.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Peasant community "Purísima Concepción de Paccha" (CCP-LO), of Yauli province, Junín-Peru, is situated between South Latitude 11 ° 31´03" and West Longitude 75 ° 53´58" (altitude 3,700) and located 10.2 km from metallurgical complex La Oroya (Figure 2), industry dedicated to poly-metallic transformation (copper, zinc, silver, lead, indium, bismuth, gold, selenium, tellurium and antimony), that emits fine particulate material (PM), loaded with heavy metals that pollute the ecosystem for more than nine decades [23,24]. PM rich in Pb and other heavy metals is deposited in the soil and water resources, and being easy transferred to the plants [25,26,17]. Figure 2 shown the geographical location o the CCP-LO.…”
Section: Study Areamentioning
confidence: 99%
“…The Pb absorption is affected by the concentration of other metals, pH and organic matter content [17] and bioaccumulation of chemical elements in plants depends on their concentrations in soil [10]. Bioaccumulation of toxic heavy metals pose a threat to human health, induce renal tumors, reduce cognitive, development, and increase blood pressure and cardiovascular diseases risk for adults [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of Cr obtained is lower than the critical permissible level which is 50 mg/kg-1 for soil recommended for agriculture by MAFF (1992). Result of Zn correlation in soils obtained in the control is far below 548.56 -642.94 obtained from hospital incinerator soil by Olayinka et al (2017). These values are far lower than the natural limits of 0.01-3.0 mg/kg in soil as given by MAFF (1992) , and lower than the tolerable soil contamination standard (SCS) and sediment quality guideline (SQG) levels of concentration (Xu-Chen et al, 2007).Positively loading in Factor 1 may be associated with flue gas while negatively loaded with Cr, Pb, Mn, and Zn may be associated with lithogenic.…”
Section: Sc = Severely Contaminated; Slt = Slightly Contaminated; Mc=mentioning
confidence: 63%
“…The result against the finding of Yaseen et al (2015) who observed that the pH of soil was acidic near the kiln and neutral farther away. Lower pH favors availability, mobility and redistribution of the metals in the various fractions due to increased solubility of the ions in acidic environment (Gunjan and Neupane, 2015;Jason et al, 2016;Olayinka et al, 2017). The result further shows that the effect of soil depths and distances were highly significant (p ≤ 0.01) on the level of soil pH in the sampled soil.The result of the effect of incinerator flue gas on heavy metals in soil varied between incinerator site and control at different distances.…”
Section: Sc = Severely Contaminated; Slt = Slightly Contaminated; Mc=mentioning
confidence: 91%